Automatic fan speed regulator / Abdul Atiq Abdul Aziz & Syed Naqib Syed Mohamed - Abdul Aziz, Abdul Atiq; Syed Mohamed, Syed Naqib (2015)
The project aims to design an automatic temperature controller for a closed area. The temperature of the closed area was controlled by the temperature sensor at a certain setting level. The setting if temperature levels are set by the user, otherwise, the temperature of a closed area is changed by the operation of fan or air conditioner . The automated fan has three different speeds. Each speed will change according to a certain level of temperature that is being set. This project is a combination of electric supply, DC fan, temperature sensor and PIC l 6F873A microcontroller unit. To complete this project, there are a few steps need to be taken which are the selections of the temperature sensor, power supply, fan, design controlling circuit using PIC 16F873A microcontroller unit, developing a source code for the microcontroller and use a suitable apparatus to design all circuit. As a conclusion, this project is to design and construct an automated fan system using temperature sensor which will be controlled by the microcontroller. The fan speed can be change according to a certain level of temperature.